Histologic analysis of resorbable blasting media surface implants retrieved from humans: a report of two cases - Jeong, Kyung-In (J Korean Assoc Oral Maxillofac Surg, 2016)
The purpose of this study is to evaluate the degree of osseointegration of resorbable blasting media (RBM) surface implants retrieved from humans. Three implants in the mandibular molar region that were surface-treated with RBM were retrieved from two patients. The implants were used to manufacture specimens in order to measure the bone-implant contact (BIC) ratio. The BIC ratios of the three implants were found to be an average of 69.0%±9.1%. In conclusion, that RBM surface implants are integrated into the host environment with histological significance and the BIC ratio of the RBM surface-treated implant was not significantly different from that of other surface-treated implants.